Identification of immediate response genes dominantly expressed in juvenile resistant and susceptible Biomphalaria glabrata snails upon exposure to Schistosoma mansoni - Ittiprasert, W.; Miller, A.; Myers, J.; Nene, Vishvanath M.; El-Sayed, N.M.; Knight, M. (Elsevier, 2010)
Resistance or susceptibility of the snail host Biomphalaria glabrata to Schistosoma mansoni is determined by the genetics of both the snail and parasite. Although Mendelian genetics governs adult resistance to infection, juvenile resistance and susceptibility are complex traits. In this study, suppression subtractive hybridization was used to construct forward and reverse cDNA libraries to identify genes involved in the immediate response of juvenile resistant (BS-90), non-susceptible (LAC2) snails, and susceptible (NMRI) snails after early exposure to S. mansoni. Expressed Sequence Tags (ESTs) were generated from the repertoire of enriched transcripts. In resistant snails, several ESTs corresponded to transcripts involved in immune regulation/defense response. While no defense related transcripts were found among juvenile susceptible snail ESTs, we detected transcripts involved in negative regulation of biological process/morphogenesis/proliferation. Differential gene expression and temporal regulation of representative transcripts were compared among snails pre- and post-exposure to either normal or attenuated miracidia using quantitative real time RT-PCR. Results showed that several transcripts, such as fibrinolytic C terminal domain, cytidine deaminase, macrophage expressed gene 1, protein kinase C receptor, anti-microbial peptide; theromacin and Fas remained up-regulated regardless of whether or not snails were exposed to normal or attenuated miracidia. While ESTs related to C-type lectin and low-density lipoprotein receptor were induced only by exposure to normal miracidia. By comparing changes in gene expression between resistant and susceptible juvenile snails responding either to normal or attenuated parasites, we can conclude that the transcription of genes associated with the intra-dermal penetration process of the snail host by invading miracidia may need to be taken into account when assessing differential gene expression between resistant and susceptible strains of B. glabrata in relation to S. mansoni exposure.